Competitive Adsorption of Carbon Monoxide and Water Vapour on MIL-100(Fe) Prepared Using a Microwave Method - Sha Wang; Xuemei Li; Zhenxia Zhao; Zhong Li (Adsorption Science & Technology)
Competitive adsorption of CO and water vapour on MIL-100(Fe) synthesized using a microwave method was systematically investigated. Adsorption equilibrium, kinetics of CO adsorption and the competitive adsorption of CO/H 2 O (V) within MIL-100(Fe) were evaluated. Results show that the unsaturated Fe(II) can enhance the adsorption amount of CO on MIL-100(Fe). The adsorbed amount of CO on MIL-100(Fe) was 2.56 mmol/g at 298 K and 10 bar with isosteric adsorption heat of 28.31–38.43 kJ/mol. MIL-100(Fe) had two kinds of adsorption sites with desorption activation energy of 53.38 and 109.5 kJ/mol for CO, respectively. The diffusion coefficient of CO through MIL-100(Fe) was approximately 2.85 times higher than that of water vapour (10.54 × 10 −16 cm 2 /s vs. 2.735 × 10 −16 cm 2 /s). The working adsorption amount of CO at 40% relative humidity was approximately 0.631 mmol/g, retaining 75% of the original adsorption amount, indicating that CO is more competitive than H 2 O on the surface of MIL-100(Fe) under humid conditions.